Development and Validation of RP-HPLC Method for Simultaneous Estimation of Ramipril, Aspirin and Atorvastatin in Pharmaceutical Preparations - Rajesh Sharma; Sunil Khanna; Ganesh P. Mishra (E-Journal of Chemistry)
A simple, sensitive, accurate and rapid reverse phase high performance liquid chromatographic method is developed for the simultaneous estimation of ramipril, aspirin and atorvastatin in pharmaceutical preparations. Chromatography was performed on a 25cm×4.6 mm i.d, 5µm particle, C18 column with Mixture of (A) acetonitrile methanol (65:35) and (B) 10 mM sodium dihydrogen phosphate monohydrate (NaH2PO4.H2O) buffer and mixture of A:B (60:40 v/v) adjusted to pH 3.0 with o-phosphoric acid (5%v/v) was used as a mobile phase at a flow rate of 1.5 ml min-1. UV detection was performed at 230 nm. Total run time was less then 12 min; retention time for Ramipril, aspirin and Atorvastatin were 3.620, 4.920 min and 11.710 min respectively. The method was validated for accuracy, precision, linearity, specificity and sensitivity in accordance with ICH guidelines. Validation revealed that the method is specific, rapid, accurate, precise, reliable, and reproducible. Calibration plots were linear over the concentration ranges 05-50 µg mL-1 for Ramipril, 05-100 µgmL-1 for aspirin and 02-20 µg mL-1 for atorvastatin. Limits of detection were 0.014, 0.10 and 0.0095 ng mL-1 limits of quantification were 0.043, 0.329 and 0.029 ng mL-1 for ramipril aspirin and atorvastatin respectively. The high recovery and low coefficients of variation confirm the suitability of the method for simultaneous analysis of the all three drugs in the dosage forms. The validated method was successfully used for quantitative analysis of marketed pharmaceutical preparations.